Index to authors (Linnaeus Tercentenary: Progress in Invertebrate Taxonomy) - Zhang, Zhi-Qiang (Zootaxa, 2007)
A total of 61 authors from 11 countires contributed to this Linnaeus tercentenary issue: 35 from USA, 7 from Australia, 6 from UK, 3 from Denmark, 2 from Canada, 2 from Germany, 1 each from Argentina, France, Italy, New Zealand, Singapore and Sweden. Among the 30 contributions, 43% are results of collaboration of two or more authors. Among the collaborative papers, 38% are the results of international collaboration.